Fruitful market mediation: challenges in implementing coopetition - Wood, Lincoln (Business Science Reference (an imprint of IGI Global), 2012)
Working in the primary sector, FruitCom is a grouping of exporters who banded together in order to break into and develop new markets. While they aim at cooperating and coordinating their activities to support actions within these new markets, the firms involved still compete in other, more established, export markets. This “coopetitive” relationship allows the group many benefits related to their ability to source material and ensure a more consistent supply, but opens them up to challenges, such as dealing with opportunistic behaviour by other members. This case outlines the background of the firms and introduces the most recent significant challenge they face. The implications of their structure are discussed with emphasis on supply, risk pooling, information sharing, and revenue- and cost-sharing. The successes gained by the group are not without sacrifice; the challenges of their operations are discussed with stress on the most recent and perhaps the most significant challenge yet.